Few-layer MoS2 nanosheet-coated KNbO3 nanowire heterostructures: piezo-photocatalytic effect enhanced hydrogen production and organic pollutant degradation. Issue 16 (4th April 2019) - Jia, Shufan; Su, Yiping; Zhang, Boping; Zhao, Zhicheng; Li, Shun; Zhang, Yunfei; Li, Pucai; Xu, Mingyuan; Ren, Ran
Abstract : MoS2 nanosheets coated KNbO3 nanowires showed enhanced piezo-photocatalytic degradation of organic pollution and hydrogen production performance. Abstract : The introduction of a piezoelectric field has been considered as a promising strategy to enhance photocatalytic activity by inhibiting the recombination of photogenerated electron–hole pairs in semiconductor photocatalysts. In this work, a novel heterostructured photocatalyst that combines piezoelectric KNbO3 nanowires and few-layer MoS2 nanosheets was designed and synthesized via a simple two-step hydrothermal method. Under simulated solar light illumination, the KNbO3 /MoS2 heterostructures showed significantly enhanced photocatalytic H2 production and organic pollutant ( e.g. rhodamine B) degradation efficiency, compared to pristine KNbO3 nanowires and MoS2 nanosheets. The photocatalytic activity can be further improved greatly by co-utilizing the solar and mechanical energy provided by ultrasonic vibration. The enhancement of photocatalytic activity can be attributed to the promotion of charge separation caused by the synergetic effect of the formation of a heterojunction and the internal piezoelectric field induced by mechanical vibration. Our findings may provide insight into strategies for designing highly efficient piezoelectric material-based nanocomposites for various photocatalytic applications such as environmental remediation and renewable energy production.